EFFECTIVENESS OF GAMIFICATION MODELS ON LEARNING MOTIVATION AND LEARNING OUTCOMES OF STUDENTS IN WAWO DISTRICT, NORTH KOLAKA REGENCY - Muh. Ali Akbar; Harry Syahputra Nasution; Ayu Purnama Wenly; Andi Helmy Ishak (Universitas Negeri Medan, 2026)
This study aims to analyze the effectiveness of the Gamification model on student learning motivation and learning outcomes in Physical Education learning in the 3T region of Wawo District, North Kolaka Regency. Low learning motivation and less than optimal student learning outcomes in physical education learning are the main problems underlying this study. The study used a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class given the gamification model treatment and the control class with conventional learning. The research instruments were a learning motivation questionnaire and a learning outcome test. Data were analyzed using the t-test and the N-Gain test to determine the effectiveness of the treatment. The results showed that there was an increase in learning motivation and learning outcomes in both groups, but the increase in the experimental group was higher than the control group. The N-Gain value showed a moderate category in the experimental group, which indicated that the gamification model was quite effective in increasing student learning motivation and learning outcomes. In conclusion, the gamification model can be an effective learning alternative to increase student engagement and learning outcomes in areas with limited facilities such as the 3T region.